A Bakhtinian take on languaging in a dual language immersion classroom. (February 2019) - King, Nicole; Ridley, Jackie
Abstract: Language brings a classroom to life and crafts the teaching and learning space. Sociocultural theories of language acquisition and learning focus on the role of language as a mediator for development. While research on languaging and translanguaging practices in English medium and multilingual classrooms is on the rise, less attention has been paid to the languaging work occurring in the translanguaging space of the dual language immersion classroom. To this end, this study explores the languaging choices of a second grade French immersion teacher as he imparts both language learning objectives and his enactment of critical peace education. This article provides a micro-discourse perspective of the speech genres utilized within a single lesson on adjectives conducted in both French and English. Data analysis revealed the ways in which students and their teacher together languaged academic French and peace education in and through different speech genres. This study demonstrates the affordances of a speech genre analysis for researching multilingualism in dual language learning settings. Implications for pedagogy and theory about bi/multilingual discourse are discussed.